Effects of PPIs use on clinical outcomes of urothelial cancer patients receiving immune checkpoint inhibitor therapy - Zhang, Lilong; Chen, Chen; Chai, Dongqi; Li, Chunlei; Kuang, Tianrui; Liu, Li; Dong, Keshuai; Deng, Wenhong; Wang, Weixing (Frontiers in Pharmacology, 2022)
Objective: Immune checkpoint inhibitors (ICIs) have recently demonstrated promising performance in improving the prognosis of urological cancer patients. The goal of this meta-analysis was to determine the impact of PPI use on the clinical outcomes of urological cancer patients receiving ICI therapy. Methods: Before 6 May 2022, the eligible literature was searched using PubMed, EMBASE, Cochrane Library, and Google Scholar. The clinical outcomes were overall survival (OS), progression-free survival (PFS), and objective response rate (ORR). Results: A total of six articles met the inclusion criteria, and of the 1980 patients with advanced or metastatic urothelial cancers (UC) included. The meta-analysis displayed that PPI use could increase the risk of progression by 50.7% (HR: 1.507, 95% CI: 1.327–1.711, p < 0.001) and death by 58.7% (HR: 1.587, 95% CI: 1.367–1.842, p < 0.001), and reduce the ORR (OR: 0.503, 95% CI: 0.360–0.703, p < 0.001) in UC patients receiving ICIs. No significant heterogeneity and publication bias existed. Sensitivity analysis proved that the results were stable and reliable. Conclusion: The meta-analysis indicated that concomitant PPI use was significantly associated with low clinical benefit in UC patients.